Defense mechanisms in the counseling process - Clark, Arthur J.; Sage eBooks (London : SAGE, 1998)
This volume presents a systematic approach to identifying and modifying client defence mechanisms in the counselling process. Examples through the book illustrate the mechanisms and therapeutic change that can result in spite of them.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Defense mechanisms (Psychology); Psychotherapy; Counseling; Electronic books